2005
DOI: 10.1128/jcm.43.4.1727-1731.2005
|View full text |Cite
|
Sign up to set email alerts
|

CHROMagar Candida Medium for Direct Susceptibility Testing of Yeast from Blood Cultures

Abstract: An evaluation was performed on 95 blood cultures positive for Candida spp. to determine the correlation of direct susceptibility testing of fluconazole versus both standardized disk diffusion and MIC methods. For direct testing, an aliquot taken from BD BACTEC Plus and/or BD BACTEC Lytic/10 bottles (Becton Dickinson [BD], Sparks, MD) positive by gram stain for yeast was subcultured to CHROMagar Candida (BD), and a 25-g fluconazole disk (BD) was placed on the plate. The area of growth inhibition surrounding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…Specimens that may be contaminated with bacteria should also be cultured on a selective medium such as inhibitory mould agar, SABHI, or BHI plus antibacterial agents (e.g., gentamicin, chloramphenicol, or ciprofloxacin plus streptomycin). CHROMagar (Hardy Diagnostics; Becton-Dickinson) is a chromogenic medium that is both selective for fungi and differential for certain Candida species (Murray, Zinchuk, & Larone, 2005;Odds & Bernaerts, 1994;Pfaller, Houston, & Coffman, 1996;Tan & Peterson, 2005). This medium inhibits bacterial growth and because different species of Candida appear as different coloured colonies it is useful in detecting mixed cultures of Candida and other fungi (Odds & Bernaerts, 1994;Pfaller et al, 1996).…”
Section: Culturementioning
confidence: 97%
“…Specimens that may be contaminated with bacteria should also be cultured on a selective medium such as inhibitory mould agar, SABHI, or BHI plus antibacterial agents (e.g., gentamicin, chloramphenicol, or ciprofloxacin plus streptomycin). CHROMagar (Hardy Diagnostics; Becton-Dickinson) is a chromogenic medium that is both selective for fungi and differential for certain Candida species (Murray, Zinchuk, & Larone, 2005;Odds & Bernaerts, 1994;Pfaller, Houston, & Coffman, 1996;Tan & Peterson, 2005). This medium inhibits bacterial growth and because different species of Candida appear as different coloured colonies it is useful in detecting mixed cultures of Candida and other fungi (Odds & Bernaerts, 1994;Pfaller et al, 1996).…”
Section: Culturementioning
confidence: 97%
“…Only one study has previously evaluated the use of fluconazole disks for direct susceptibility testing of Candida species; however, that study used CHROMagar, which is not a recommended susceptibility testing medium (26). Another approach has been the direct inoculation of Vitek antifungal cards for susceptibility testing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physicians felt reassured in continuing patients on fluconazole if the MIC demonstrated susceptibility of the Candida isolate. On the other hand, detection of resistance to fluconazole is clearly desirable, and early recognition of resistance in clinical isolates may contribute to successful clinical and microbiologic outcomes (86,101,112). Hadley et al (28) reported the use of real-time antifungal susceptibility testing in modifying treatment decisions in several patients with invasive fungal infections.…”
Section: Clinical Importance Of Antifungal Susceptibility Testing As mentioning
confidence: 99%
“…The simplicity and flexibility of disk diffusion testing makes it a very appealing method for use in the clinical laboratory (72,74,75). Results are clearly available in real time (i.e., 24 h), and innovative efforts to integrate this form of antifungal testing into the work flow of the clinical laboratory are ongoing (101). Thus, fluconazole disk diffusion testing is being performed in clinical laboratories throughout the world as an aid in selecting the most efficacious, nontoxic, and costeffective therapy for treatment of candidiasis.…”
Section: Clinical Importance Of Antifungal Susceptibility Testing As mentioning
confidence: 99%